OPTIMASI MORINGA GUM DAN GLISERIN DALAM SEDIAAN MUCOADHESIVE BUCCAL FILM DILTIAZEM HIDROKLORIDA - Lusia Oktora Ruma Kumala Sari; Lidya Ameliana; Putri Mustika Nandani (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2023)
Moringa Gum is a gum derived from the Moringa oleifera tree which can be used as a stabilizer, binder, mucoadhesive, disintegrant, sustained release and controlled release matrix. Diltiazem Hydrochloride is a drug with low bioavailability and has a low plasma half-life (3-4 h). The bioavailability and half-life of Diltiazem Hydrochloride can be improved by buccal film mucoadhesive formulation. In this study, a combination of natural polymers, namely Moringa Gum and glycerin plasticizer, was used to produce a film with swelling, mucoadhesive properties and also good folding resistance. This studi was conducted to optimize Moringa Gum and glycerin to see the release profile of Diltiazem Hydrochloride in the muchoadhesive buccal film. The formulation was carried out using the solvent casting method with optimization using a design expert while verification of the optimum formula was carried out using a one sample t test with a confidence level of 95% with the condition that the significance was p>0,05. The optimum formula obtained from the amount of polymer Moringa Gum is 75 mg and the plasticizer glycerin is 5 mg. The results of the FTIR test showed that there was no interaction between Diltiazem Hydrochloride and the moringa gum polymer. As for the release test results, the release percentage was 99.69% by following the Higuchi release model. This study concludes is that buccal film was successfully prepared using a combination of moringa gum and glycerin with its potential to increase the bioavailability and half-life of Diltiazem Hydrochloride by prolonging the contact time and controlling the release. Kata Kunci Diltiazem Hidroklorida; Mucoadhesive Buccal Film; Moringa Gum; Gliserin